Efficacy of an inactivated whole-cell injection vaccine for nile tilapia, Oreochromis niloticus (L), against multiple isolates of Francisella noatunensis subsp. orientalis from diverse geographical regions. Issue 89 (June 2019) - Shahin, Khalid; Shinn, Andrew P.; Metselaar, Matthijs; Ramirez-Paredes, Jose Gustavo; Monaghan, Sean J.; Thompson, Kim D.; Hoare, Rowena; Adams, Alexandra
Abstract: Francisellosis, induced by Francisella noatunensis subsp. orientalis ( Fno ), is an emerging bacterial disease representing a major threat to the global tilapia industry. There are no commercialised vaccines presently available against francisellosis for use in farmed tilapia, and the only available therapeutic practices used in the field are either the prolonged use of antibiotics or increasing water temperature. Recently, an autogenous whole cell-adjuvanted injectable vaccine was developed that gave 100% relative percent survival (RPS) in tilapia challenged with a homologous isolate of Fno . In this study, we evaluated the efficacy of this vaccine against challenge with heterologous Fno isolates. Healthy Nile tilapia, Oreochromis niloticus (∼15 g) were injected intraperitoneally (i.p.) with the vaccine, adjuvant-alone or phosphate buffer saline (PBS) followed by an i.p. challenge with three Fno isolates from geographically distinct locations. The vaccine provided significant protection in all groups of vaccinated tilapia, with a significantly higher RPS of 82.3% obtained against homologous challenge, compared to 69.8% and 65.9% with the heterologous challenges. Protection correlated with significantly higher specific antibody responses, and western blot analysis demonstrated cross-isolate antigenicity with fish sera post-vaccination and post-challenge. Moreover, a significantly lower bacterial burden was detected by qPCR in conjunction with significantly greater expression of IgM, IL-1 β, TNF-α and MHCII, 72 h post-vaccination (hpv) in spleen samples from vaccinated tilapia compared to fish injected with adjuvant-alone and PBS. The Fno vaccine described in this study may provide a starting point for development a broad-spectrum highly protective vaccine against francisellosis in tilapia. Editor highlights: Efficacy of an injectable vaccine of Francisella noatunensis subsp. orientalis with adjuvant was tested against challenge with three different Fno isolates in Nile tilapia. The developed vaccine stimulated innate and adaptive immunity post-vaccination and provided protection against homologous and heterologous Fno isolates. Significantly higher IgM levels and significantly lower bacterial burden following i.p. vaccination and challenge correlated with protection, suggesting a protective role of antibody-mediated immunity against Fno in Nile tilapia.